2018
DOI: 10.1002/anie.201800272
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilicity Regulates the Stealth Properties of Polyphosphoester‐Coated Nanocarriers

Abstract: Increasing the plasma half-life is an important goal in the development of drug carriers, and can be effectively achieved through the attachment of polymers, in particular poly(ethylene glycol) (PEG). While the increased plasma half-life has been suggested to be a result of decreased overall protein adsorption on the hydrophilic surface in combination with the adsorption of specific proteins, the molecular reasons for the success of PEG and other hydrophilic polymers are still widely unknown. We prepared polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(134 citation statements)
references
References 33 publications
3
127
0
2
Order By: Relevance
“…NPs' properties of interest include size, 12 surface charge and functionalization, 11 stabilizing surfactants, 13 and hydrophilicity. 14 On the other hand, the proteins' properties of interest address their amphiphilic character, which leads to screening of hydrophobic parts of the protein from the surrounding water. 15 Similarly, smaller hydrophobic molecules can be transported by amphiphilic proteins such as lipids attached to apolipoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…NPs' properties of interest include size, 12 surface charge and functionalization, 11 stabilizing surfactants, 13 and hydrophilicity. 14 On the other hand, the proteins' properties of interest address their amphiphilic character, which leads to screening of hydrophobic parts of the protein from the surrounding water. 15 Similarly, smaller hydrophobic molecules can be transported by amphiphilic proteins such as lipids attached to apolipoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Additionally,byvarying the chemical structure of the polymers used for stealth functionalization, it was shown that the hydrophilicity of the chains (and thus the material available for interaction) plays ak ey role in mediating the specific enrichment of stealth proteins:T he higher the polymer hydrophilicity,t he more clusterin and apo AI proteins were found in the corona. [145] With these results,c omputer simulations can be used to understand the molecular interaction of PEG with clusterin and other proteins. [142] Hereby,t he list of adsorbed proteins can be correctly predicted.…”
Section: Understanding and Predicting The Specificity Of The Protein mentioning
confidence: 99%
“…Dann versuchen Immunzellen, diese markierten Fremdstoffe zu eliminieren. [145] Mit diesen Ergebnissen kçnnen Computersimulationen verwendet werden, um die molekulare Wechselwirkung von PEG mit Clusterin und anderen Proteinen zu verstehen. [143] Poly(ethylenglykol) (PEG) war der Prototyp dieser Oberflächenmodifikationen.…”
Section: Verstehen Und Vorhersagen Der Spezifitätder Proteinkorona Vounclassified
“…[13] Durch die Va riation der chemischen Struktur von Polymeren, die für die Stealth-Funktionalisierung verwendet wurden, konnte außerdem gezeigt werden, dass die Hydrophilie der auf der Oberfläche angebrachten Ketten (und damit das fürd ie Interaktion verfügbare Material) eine Schlüsselrolle bei der spezifischen Anreicherung von Stealth-Proteinen spielt:J e hçher die Hydrophilie des Polymers,d esto mehr Clusterin und ApoAI wurden in der Korona gefunden. [145] Mit diesen Ergebnissen kçnnen Computersimulationen verwendet werden, um die molekulare Wechselwirkung von PEG mit Clusterin und anderen Proteinen zu verstehen. [142] Hiermit kann die Liste der adsorbierten Proteine korrekt vorhergesagt werden.…”
Section: Verstehen Und Vorhersagen Der Spezifitätder Proteinkorona Vounclassified